Towards a drug distributor price reference index: A 2023 survey of pricing discrepancies for region 02 medicines procured from NCR and local distributors, Philippines - Jinky Marie Tuliao Chua, Julius Tamayao Capili, Ma. Angelita Saquing Rabanal, Lily Ann Caldez Mallabo, Jay Emmanuel Laciste Asuncion (Journal of Applied Pharmaceutical Science, 2025)
Drug prices are a key barrier to healthcare access in the Philippines, where out-of-pocket payments remain the main form of health spending. This study assessed price variations between drug distributor prices for commonly procured medicines in Region 02 and the National Capital Region (NCR), and the National Drug Price Reference Index (DPRI). A cross-sectional survey was conducted from June to December 2023 using 2022 commonly procured medicines from 18 public health facilities in Region 02. Price and availability data of both essential and nonessential medicines were gathered from 50 Food and Drug Administration-registered drug distributors in Region 02 and NCR. The top 15 of the 591 commonly procured medicines were selected for comparison. Six had distributor prices below the DPRI; however, only one (Gliclazide 30 mg tablet) had a statistically significant difference (p < 0.05), with a large effect size (Cohen’s d = −2.90). The remaining five showed small to negligible effect sizes and nonsignificant p-values (p > 0.05). Nine medicines were within the DPRI range but not below the lowest reference price. Three essential medicines, including insulin and two anti-tuberculosis kits, were available from only a few surveyed distributors, indicating limited access across the network. The findings reveal pricing disparities and highlight gaps in access to critical medicines; hence, continuous price monitoring and support the establishment of a Drug Distributor Price Reference Index are recommended. This is to inform cost-effective and equitable procurement policies.
Keywords: Drug prices, pharmaceutical distribution, pricing discrepancies, drug price reference index, Philippines